Geographical differentiation and genetic diversity of Algerian pearl millet assessed with microsatellites - Kirouani, Abderrezzak; Babay, Elyes; Ouldkiar, Redha; Belhadi, Badreddine; Souilah, Rachid; Boukhalfoun, Leila; Djabali, Djaafar; Nadjemi, Boubekeur (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Pearl millet, a drought-tolerant cereal, is a crucial role in food security, in arid and semi-arid regions. Despite its global significance, genetic diversity of Algerian pearl millet populations remains underexplored. This study assessed the genetic diversity of 22 pearl millet genotypes from four distinct Saharan agroclimatic zones in Algeria using 24 SSR markers. A total of 87 alleles were detected, with an average of 3.62 alleles per locus and polymorphic information content (PIC) values ranging from 0.043 to 0.815, indicating substantial genetic variability. Analysis of Molecular Variance (AMOVA) revealed greater genetic variance within individuals than among them. Genotypes from Tamanrasset and In Salah exhibited higher diversity than those from Oued Souf and Adrar, with private and rare alleles underscoring the impact of geographic isolation. Cluster analysis and principal coordinates analysis (PCoA) grouped genotypes by geographic origin, identifying five major genetic groups, confirming patterns of gene flow and local adaptation. Populations from Niger and India were highly genetic distant from Algerian landraces making them promising candidates for heterotic hybrid development. These findings provide insights for broadening the genetic base of breeding strategies targeting yield and stress resilience in pearl millet.